Fur Represses Vibrio cholerae Biofilm Formation via Direct Regulation of vieSAB, cdgD, vpsU, and vpsA-K Transcription - Gao, He; Ma, Lizhi; Qin, Qin; Qiu, Yue; Zhang, Jingyun; Li, Jie; Lou, Jing; Diao, Baowei; Zhao, Hongqun; Shi, Qiannan; Zhang, Yiquan; Kan, Biao (Frontiers in Microbiology, 2020)
Attached Vibrio cholerae biofilms are essential for environmental persistence and infectivity. The vps loci (vpsU, vpsA-K, and vpsL-Q) are required for mature biofilm formation and are responsible for the synthesis of exopolysaccharide. Transcription of vps genes is activated by the signaling molecule bis-(3'-5')-cyclic di-GMP (c-di-GMP), whose metabolism is controlled by the proteins containing the GGDEF or/and EAL domains. The ferric uptake regulator (Fur) plays key roles in the transcription of many genes involved in iron metabolism and non-iron functions. However, its roles in biofilms of vibrios have been not documented. In this study, phenotypic assays demonstrated that Fur, independently of iron, decreases in vivo c-di-GMP levels and inhibits in vitro biofilm formation by V. cholerae. Fur box-like sequences were detected within the promoter-proximal DNA regions of vpsU, vpsA-K, vieSAB and cdgD, suggesting that transcription of these genes may be under the direct control of Fur. Indeed, the results of luminescence, qPCR, EMSA and DNase I footprinting assays demonstrated that Fur binds to the promoter-proximal DNA regions of vpsU, vpsA-K, and cdgD, to repress their transcription, whereas it activates the transcription of vieSAB in a direct manner. The cdgD and vieSAB encode proteins with GGDEF and EAL domains, respectively. Thus, data presented here highlight a new physiological role for Fur that acts as a repressor of V. cholerae biofilm formation, which is mediated by decreasing the production of exopolysaccharide and the intracellular levels of c-di-GMP.